Pengaruh Disiplin Dan Beban Kerja Terhadap Kinerja Karyawan PT. Bank Negara Indonesia (Persero) Kantor Cabang Pasar Mayestik Jakarta - Kurnia Anugrah Prayoga; Bachtiar Arifudin Husain (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The emergence of stronger business competition requires companies to improve the performance of Human Resources, there are several things that influence work discipline and workload. The purpose of this study was to determine whether there is a positive and significant influence between Discipline and Workload either partially or simultaneously on employee performance at PT Bank Negara Indonesia (Persero) Tbk Mayestik Market Branch Office - Jakarta. This study uses associative quantitative research methods where the data obtained in the form of questionnaires processed using the SPSS 25 application. the result There is an influence of Discipline on employee performance at PT. Bank Negara Indonesia (Persero) Tbk Mayestik Market Branch Office - Jakarta, There is an influence of Workload on employee performance at PT. Bank Negara Indonesia (Persero) Tbk Mayestik Market Branch Office - Jakarta, There is an influence of Discipline and Workload on employee performance at PT. Bank Negara Indonesia (Persero) Tbk Mayestik Market Branch Office - Jakarta, there is a simultaneous positive and significant influence between Discipline and Workload variables on employee performance